Analysis of the Influence of Investment, Net Exports and Exchange Rates on GRDP in 5 Provinces on the Island of Sumatra - Tia Apriliya Ningsih; Mohammad Ridwan (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This study aims to examine the influence of investment, net exports, and exchange rates on the Gross Regional Domestic Product (GRDP) in the five major provinces located on Sumatra Island. The selection of these provinces was based on their substantial size and significant economic contribution to the GRDP of Sumatra Island. Sumatra Island is known for its vast natural resource potential, which holds considerable economic significance. The primary objective of this study is to investigate the impact of investment, net exports, and exchange rates on the GRDP of these five provinces within the period spanning from 2007 to 2022. The data analysis method employed in this research involves panel data, using secondary data gathered from 2007 to 2022. The data analysis was conducted using Eviews9 software, and the model used in this study is the Random Effects Model (REM). The research findings demonstrate that investment, net exports, and exchange rates wield significant influence over the GRDP in these five provinces of Sumatra Island. These results underscore the pivotal role these factors play in shaping the economic development of the region.